Effects of Gender Awareness Aesthetic Consciousness on the Appearance Management Behaviors in the Male University Students - Kim, Kyung-Yun; Park, Hae-Ri; Lim, Cheong-Hwan (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: This study was aimed to investigate the effects of gender awareness aesthetic consciousness on the appearance management behaviors in the male university students, who are future consumers in men’s beauty market rapidly growing at the present so as to use the fundamental data leading the trend of men’s beauty.Methods: In this study, the subjects were 284 male university students, gender awareness aesthetic consciousness was classified with its lower levels including appearance capability and aesthetics/plastic surgery and was analyzed whether it affected the appearance management behaviors including passive and active management behaviors. To do so, descriptive statistics, reliability analysis, and hierarchical regression analyses were performed.Finding: The aesthetic consciousness has been shown to affect appearance management behaviors. In terms of grades, those who tried to get jobs showed higher aesthetic consciousness and appearance management behaviors. The idea that appearance meant the capability showed high among aesthetic consciousness while the awareness of aesthetics/ plastic surgery showed low. As the idea that appearance meant the capability was higher, active management behaviors were occurred more. As the awareness of aesthetics/ plastic surgery showed higher, they showed passive management behaviors more.Improvements: In this study, it was shown that a variety of variables that can affect the appearance management behaviors in the male university students should be added, and studies on their relationship and effectiveness should be conducted.